A Diastereoselective Mizoroki–Heck Reaction for Synthesis of Spirooxindole-Based Nonnatural Amino Acids Using a Boc-Protected Amine Chiral Auxiliary - Lindman, Jens; Puthiyaparambath, Sharathna; Gising, Johan; Odell, Luke R.; Larhed, Mats (Synlett, 2025)
Nonnatural amino acids are pivotal for expanding the functional diversity of peptides and proteins, enabling novel therapeutic opportunities. Mono-Boc-protected spirocyclization precursors have been developed as versatile intermediates for the diastereoselective synthesis of spirooxindole-based nonnatural amino acids by the Mizoroki–Heck reaction. Catalytic hydrogenation produced cyclopentyl derivatives, expanding the diversity of these amino acids. Furthermore, one spirooxindole derivative was incorporated into a tripeptide by solid-phase peptide synthesis on Rink amide resin to demonstrate its potential in peptide modification and drug development.
Keywords: amino acids; diastereoselectivity; asymmetric synthesis; Mizoroki–Heck reaction; spirooxindoles; palladium catalysis